Analysis of early-design timber models for sound insulation. (August 2022) - Châteauvieux-Hellwig, Camille; Abualdenien, Jimmy; Borrmann, André
Abstract: Timber construction is associated with a low carbon footprint and offers a high degree of sustainability. However, it poses challenges considering sound insulation. Acoustic analyses, which could require major expensive and time consuming changes in the building design, are typically performed once the design is already in the detailed stage. By using building information modelling (BIM), it is possible to shift the planning of the building physics, including acoustic analysis, to earlier phases. To make this possible, building models must include all the information necessary to perform acoustic analyses. One important part of acoustic analysis is identifying junctions between elements and map them to the junction types in standards. Until now, this investigation involves tedious manual processing for extracting multiple topological dependencies between different elements. Hence, this paper presents a framework for a seamless workflow between building models and acoustic analysis tools, based on an analysis of data models. The framework extracts and analyzes the element types, their geometry, and the connections of the individual elements in relation to each other. Through topological reasoning, along with a set of logical rules, the proposed framework identifies fifteen types of junctions, which can be distinguished acoustically for timber construction. The approach was evaluated in a prototypical implementation using a real-world model based on Industry Foundation Classes (IFC) as an example, in which the potential connection types were successfully extracted. This paper shows that junction analysis can be done with a geometric analysis to fill in missing semantic information about junctions of elements from the original data model.